2015
DOI: 10.1007/8904_2015_506
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Lipid Accumulation Detected by MRS in a Child with Carnitine Palmitoyltransferase 2 Deficiency: A Case Report and Review of the Literature on Genetic Etiologies of Lipid Peaks on MRS

Abstract: The majority of lipids in the brain are located in the bilayer membranes. These lipids are not visible by magnetic resonance spectroscopy since they have restricted mobility. Only mobile lipids, such as cholesterol esters or triglycerides in neutral lipid droplets, have enough rotational freedom to generate a signal on spectroscopy. These signals are detected as peaks at 1.3 ppm, originating from the methylene groups in the fatty acid chain, and 0.9 ppm, originating from the distal methyl group. We review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Certain IEMs can be accompanied by structural brain anomalies identifiable by brain MRI, such as a dysgenetic corpus callosum seen commonly in patients with pyruvate dehydrogenase complex deficiency or glycine encephalopathy (23). Brain magnetic resonance spectroscopy can sometimes point toward the right diagnosis, as has been reported in patients with GABA transaminase deficiency (24), fatty acid oxidation disorders (25), mitochondrial disease or glycine encephalopathy (26). Table 2 provides a summary of the salient clinical, laboratory, electrographic, and neuroimaging finding of the most common metabolic epilepsies.…”
Section: Resultsmentioning
confidence: 99%
“…Certain IEMs can be accompanied by structural brain anomalies identifiable by brain MRI, such as a dysgenetic corpus callosum seen commonly in patients with pyruvate dehydrogenase complex deficiency or glycine encephalopathy (23). Brain magnetic resonance spectroscopy can sometimes point toward the right diagnosis, as has been reported in patients with GABA transaminase deficiency (24), fatty acid oxidation disorders (25), mitochondrial disease or glycine encephalopathy (26). Table 2 provides a summary of the salient clinical, laboratory, electrographic, and neuroimaging finding of the most common metabolic epilepsies.…”
Section: Resultsmentioning
confidence: 99%
“…The main spectroscopy peaks at 1.3 ppm originate from the methylene groups in the fatty acid chain, while those at 0.9 ppm originate from distal methyl groups. 10 We reported elevated neuroinflammation throughout the basal ganglia and some cortical regions in CRPS patients in a previous study 3 and found an association between lipids in brains and neuroinflammation. Mobile lipids visible on MRS can be seen in various acquired disorders, such as areas of necrosis within brain tumors, 12 and demyelinating diseases, such as multiple sclerosis.…”
Section: Discussionmentioning
confidence: 64%
“…Only mobile lipids in neutral lipid droplets have sufficient rotational freedom to generate a signal on spectroscopy; these signals are detected as peaks at 1.3 ppm, originating from the methylene groups in the fatty acid chain, and at 0.9 ppm, originating from distal methyl groups. 10 We reported increased neuroinflammation throughout the basal ganglia and some cortical regions in CRPS patients in a previous study 3 and found an association between lipids in the brain and neuroinflammation. Considering that the somatosensory system involved in pain perception includes the thalamus, the primary somatosensory cortex, and the insula 11 and that the thalamus is the region that connects peripheral regions directly, we focused on the right and left thalamic regions.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…2e), and in vivo 1 H-MRS brain analysis of CamkIIα-Pfkfb3 mice showed increased lipid 13a and lipid 13b signals (Extended Data Fig. 3b), which denotes enhanced abundance of lipid droplets 29,30 . To confirm this, we assessed by western blotting the levels of perilipin 2 (PLIN2), a lipid droplet-coating protein that limits the access of lipases, favouring the accumulation of lipids 31 .…”
Section: Lettermentioning
confidence: 96%